(untitled) (Nigerian Journal of Cooperative Economics and Management, 2023)
This paper evaluates total economic recovery through cooperative sustainability. The aim is to investigate the ways in which cooperatives can act as agents towards sustainable community development. The paper is a descriptive survey, which involves the collection of data for the purpose of describing the role of cooperative societies in economic development. The paper posits that for over 160 years now cooperatives have been an effective way for people to exert control over their economic livelihoods as they play an increasingly important role in facilitating job creation, economic growth and social development. The paper concludes that to be effective and successful, cooperatives must continuously achieve two inter-related goals: enhance viability and improve ability to service its members; and remain an economically viable, innovative and competitive enterprise. The study recommends that government should give maximum financial and non-financial supports to cooperative societies to enhance sustainability.